Highly Dense, Transparent α‐Al2O3 Ceramics From Ultrafine Nanoparticles Via a Standard SPS Sintering. Issue 4 (15th March 2013) - Roussel, Nicolas; Lallemant, Lucile; Chane‐Ching, Jean ‐Yves; Guillemet‐Fristch, Sophie; Durand, Bernard; Garnier, Vincent; Bonnefont, Guillaume; Fantozzi, Gilbert; Bonneau, Lionel; Trombert, Sandrine; Garcia‐Gutierrez, Domingo; Krell, A.
<x xml:space="preserve">Abstract</x> Using discrete, ultrafine alumina, highly dense transparent (71% real in‐line transmission, RIT, λ = 640 nm) ceramics were achieved with grain size as small as 260 nm using standard SPS sintering. We show that use of La3+ as a dopant greatly reduces sensitivity to the sintering temperatures. Transparent alumina were achieved in a large range of sintering temperatures, 1140°C < T < 1200°C, thus providing better reliability and flexibility into the fabrication of large sintered transparent ceramic bodies.